Chemical constituents of Aglaia exima / Loong Xe-Min - Loong, Xe-Min (2012)
A preliminary study on the chemical constituents of Aglaia exima was performed. The leaves of Aglaia exima was extracted in three different solvents: hexane, dichloromethane and methanol. The fractionation of the hexane extract of the leaves of Aglaia exima collected in Terengganu led to the isolation of one new cycloartane triterpenoid; cycloart-24-ene-26-ol-3-one 203 and seven known compounds, which are four cycloartane triterpenoids; 24(E)-cycloart-24-ene-3β,26-diol 199, vaticinone 200, schizandronic acid 201, 24(E)-3β-hydroxycycloart-24-ene-26-al 204, one dammarane triterpenoid; cabraleahydroxylactone 202 and two steroids; β-sitosterol 205 (sterol) and stigmast-5-ene-28-one 207 (sterol). The structures of compounds were analyzed and elucidated by using spectroscopic methods; 1D and 2D NMR, mass spectrometry, infrared spectrometry and X-ray. The hexane, dichloromethane and methanol extracts from leaves of Aglaia exima were subjected to biological activity screening. All isolated compounds were measured in vitro for their cytotoxic activities against eight cancer cell; lung (A549), prostate (DU-145), skin (SK-MEL-5), pancreatic (BxPC-3), liver (Hep G2), colon (HT-29), breast (MCF-7) and (MDA-MB-231). The new cycloartane triterpenoid, cycloart-24-ene-26-ol-3-one 203, showed potent cytotoxic activity against colon (HT-29) cancer cell line (IC50 11.5 μM).